Black Orchid - Gaiman, Neil.; McKean, Dave.; Klein, Todd. (New York, NY DC comics/Vertigo, 2012)
A plant/human hybrid superhero called Black Orchid goes on a spiritual journey in the wake of her death, during which she reviews her life, investigates her origins, and is given the opportunity to avenge herself.
Introduction by Mikal Gilmore -- ch. 1. One thing is certain -- ch. 2. Going down ... -- ch. 3. Yes ... -- Acknowledgements.
Keywords: Graphic novels; Comic books, strips, etc. -- United States; Graphic novels